Unfolding Filipino Parents’ Acceptance Process of their Children with Disability - Sarmiento , Patricia Aubrey; Ancho, Inero; Dy, Marison Felicidad; Ferido , Melissa; Pelegrina , Daisy (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Having a child with a disability does not happen to all families. Parents of children with disabilities have to go through an acceptance process without a specific blueprint as parents use different coping mechanisms and are influenced by several factors. This study aims to analyze parents' acceptance process and their aspirations for their child with CWD. Seven participants were selected through snowball sampling method and underwent semi-structured in-depth interviews for data collection while the instrument used was an interview sheet. Data analysis was conducted using the interpretive phenomenology (IPA) approach which resulted in high-level themes. The results showed that the process of parental acceptance includes different internal processes that are categorized into superordinate themes namely: discovering disability, facing reality, reconstructing a new normal, dealing with the situation, making peace, hoping for a better future, and advocating for an inclusive tomorrow. It can be concluded that parents of children with disabilities (CWD) face a unique and complex process of acceptance after learning of their child's disability. The implication of this study is the importance of interventions that focus on increasing social support and adequate health facilities for families with CWD.